Hydrothermal Alteration of Epithermal Gold Deposit at Dalangturu and Suruh areas, Trenggalek Regency, East Java, Indonesia - , Ph. Phoumephone ([Yogyakarta] : Departemnts of Geological Engineering Faculty of E, 2009)
The report of high potential for epithermal gold deposit indicated vein float assaying gold content up to 12 g/t and 10 g/t at Dalangturu, Suruh respectively. Extensive area (2x3 km2)of replacement silicification and hydrothermal breccias associated with anomalous pathfinder metal (As, Sb, Hg) content. The purposes are to map hydrothermal alteration and geology in order to understand the nature of the paleo-hydrothermal activity, provide guide lines for further explorations. The rock type that defined the geology included volcanic rocks, hydrothermal breccias, limestone, and sedimentary rocks. Petrological and geochemical indicate the protolith of the gold and base metals mineralization occurs in narrow, colloform-crustiform banded quartz-chalcedony veins hosted by andesite flows-breccias and tuffs of the Oligocene- Miocene age. Hydrothermal activity could defined into four hydrothermal alteration zones which supported by petrology, whole rock geochemistry, XRD analysis and field oDservation. The sensitive clay minerals indicate these alteration zones are formed under temperature 80-220&deg